Protective Factors for Early Childhood Caries in 3-Year-Old Children in Poland - Olczak-Kowalczyk, Dorota; Gozdowski, Dariusz; Turska-Szybka, Anna (Frontiers in Pediatrics, 2021)
Background: Early childhood caries (ECC) remains highly prevalent in preschool children worldwide. Dental caries affects every second 3-year-olds in Poland. The aim of the study was to assess protective factors for ECC in 3-year-olds. Methods: A cross-sectional survey was conducted in 2017 among 3-year-olds attending kindergartens in all 16 provinces of Poland. The questionnaire included socioeconomic factors, and oral health behaviors. Decayed, missing due to caries and filled teeth and surfaces were assessed. Caries indices (dmft and dmfs), percentage of caries-free and severe ECC (S-ECC) were calculated. The Student's t-test, Spearman correlation, univariate and multivariate logistic regression (the odds ratios (OR) and adjusted odds ratios (AOR): confounding factors: socioeconomic conditions, oral health behaviors) were performed; p < 0.05. Results: A total of 1,638 children were included. ECC was confirmed in 41.1%; S-ECC in 23.4%. The dmft index was 1.85 ± 3.14, dmfs = 2.99 ± 6.56. Spearman correlation [socioeconomic factors, especially mother's education (r = −0.148, p < 0.001) and family's economic status (r = −0.071, p = 0.004)], despite were statistically significant, indicate very weak relationships with dmft index. After 12th month of life not giving any beverages before bedtime and at night, but water or unsweetened milk only, healthy snacking (sandwiches, fresh fruit), or water on a daily basis decreases the probability of caries development (for S-ECC: OR = 0.37, AOR = 0.47, AOR2 = 0.37; p < 0.01), even if inappropriate dietary behaviors or hygiene practices were simultaneously present. Brushing of a child's teeth twice a day lowered the odds of caries (for S-ECC: OR = 0.78, p = 0.031; AOR = 0.81, p = 0.081; AOR2 = 0.84, p = 0.131), but this effect was less intense when inappropriate dietary behaviors were accounted for. Children of parents with good self-assessment of their teeth were more often caries-free (61.4 vs. 42.9%; p = 0.006) and had lower dmft indices (1.67 vs. 2.93; p = 0.002). Conclusions: Preventing a child after 12th month of life from getting any beverages before bedtime, water or unsweetened milk only, sandwiches and fresh fruit as snacks, or water given to on a daily basis, tooth brushing twice a day decrease the odds of caries in 3-year-olds. Diet appears to have primary significance in the etiology of ECC, since tooth brushing can only partly attenuate the impact of inappropriate dietary behaviors on dental caries. Children are more often caries-free and have lower severity of caries if their parents' dentition is self-assessed as healthy.